Epitaxial growth and room-temperature ferromagnetism of quasi-2D layered Cr4Te5 thin film. (21st April 2022) - Wang, Jing; Wang, Weiyuan; Fan, Jiyu; Zheng, Huan; Liu, Hao; Ma, Chunlan; Zhang, Lei; Tong, Wei; Ling, Langsheng; Zhu, Yan; Yang, Hao
Abstract: Large-scale growth of two-dimensional (2D) ferromagnetic thin films will provide an ideal platform for studying 2D magnetism and active spintronic devices. However, controllable growth of 2D ferromagnets over large areas faces tremendous challenges. Herein, we report a large-area growth of 2D ferromagnetic single-crystal thin films Cr4 Te5 on Al2 O3 (0001) substrates using pulsed laser deposition. X-ray diffraction patterns and atomic force microscopy detection confirm that all thin films have high quality epitaxy together with being atom-level smooth. Magnetic measurements show the persistence of ferromagnetic ordering state to above room temperature, with a Curie temperature ∼320 K, atomic magnetic moment ∼0.307 μ B /Cr, and the easy-magnetization axis in the film plane. Comparing with bulk Cr4 Te5 single-crystal, the critical exponent β = 0.491 indicates that the magnetic interactions of the thin film obey the mean-field model rather than the 3D Heisenberg model. This work will open an avenue for growing large-scale 2D ferromagnets and developing room temperature 2D magnet-based nanodevices.